The 11th hour - Conners, Nadia; Petersen, Leila Conners; DiCaprio, Leonardo; Castleberry, Chuck; Gerber, Brian; Warner Independent Pictures; Appian Way (Firm); Tree Media Group; Warner Home Video (Firm) ([United States] : Warner Home Video, 2008)
Explores the indelible footprint that humans have left on this planet, and the catastrophic effects of environmental neglect and abuse, and calls for restorative action through a reshaping of human activity
Title from title screen
Photography, Peter Youngblood Hills, Andrew Rowlands, Brian Knappenberger ; editors, Pietro Scalia, Luis Alvarez y Alvarez ; music, Jean-Pascal Beintus, Eric Avery
Leonardo DiCaprio, narrator ; Kenny Ausubel, Wangari Matthai, Sandra Postel, interviewees
In English with optional English, French, or Spanish subtitles
Keywords: Environmental responsibility; Environmental degradation; Global warming; Climatic changes; Human ecology; Earth -- Effect of human beings on